Benchmarking between two different hospitals on health risk management in the covid-19 emergency. (20th October 2021) - Nasi, G; Brandimarte, G; Marrone, R; Sponzilli, A; Sorbara, D; Benedetti, P; Grande, D; Brando, C; D'Avino, A; Parrocchia, S
Abstract: Iusse: The strategies adopted during COVID19 emergencies by two different hospitals in the Lazio Region are presented: S. Maria Goretti Hospital (SMGH) directly managed by the ASL Latina, hub and centre of the Emergency Department, and Cristo Re Classified Hospital (CRH), accredited in the territory of the ASL Roma1. Description of the problem: SMGH has been identified as COVID19 Intervention Hospital. CRH initially was a No-COVID support structure, then included in the COVID19 network. During the COVID19 emergency, the directors of both hospitals had to simultaneously ensure activity as usual, COVID19 recovery and risk management. Results: SMGH, while continuing the emergency, oncological, pregnancy, paediatrics and outpatient activities, COVID19 patients was isolated on 7 different floors/areas. Moreover was defined: chain of command; clinical admission criteria; COVID19 multi-professional and support teams, roles, skills and specific training; health surveillance; environmental hygiene, safety paths/procedures, vaccinal center and much more. CRH, while continuing minimum programmed activities to reduce waiting lists, in the first epidemic phase was created 4 tensile structures for Pre-triage and COVID pathways, respiratory isolation area for supsected patient; transfer admission for emergency networks, clean-dirty pathway. Moreover in the second phase, was activated beds of COVID19 network and 4 technical beds OBI; the 'Walk-in' for antigenic testing, with molecular confirmation <24h and infectious counselling; multi-disciplinary and specialist support teams, training courses, health surveillance, vaccinal center and much more. Lessons: During COVID19 pandemic, risk management skills linked to the technical-organisational strategy of hospital directors, making it possible to reprogramme their structure in a short period of time with flexibility and resilience of the whole organization. Key messages: Specific skills and roles, both hygienic and organizational, are essential to risk management in hospitals during epidemic emergencies. The multidisciplinarity, flexibility and modularity of the hospital structure are the organizational bases in cases of pandemics.